Desmoid-type fibromatosis tumor in children: A narrative review of the literature - Mohammed Awadh Bin-Salah; Abdulrahman Ibrahim Alhilal; Faris Abdullah Alghamdi; Yazeed Musaid Aldeghaither; Bader Fatani (Saudi Journal of Oral Sciences)
Desmoid tumors (DTs), or aggressive fibromatosis, are rare soft-tissue tumors known for their tendency to recur postsurgery. Originating in musculo-aponeurotic tissue, they can appear in various body locations. Their development is linked to multiple factors, including genetics, hormones, environment, and potentially viral infections. While existing literature addresses DTs, there is a notable gap in narrative reviews focused on diagnosis, treatment, and outcomes specifically for children. This review aims to comprehensively evaluate desmoid-type fibromatosis in pediatric patients.